Analisis Pengaruh Inflasi, Suku Bunga, dan Nilai Tukar terhadap Pertumbuhan Ekonomi di Indonesia - Alvianus Kristian Sumual; Windi Aulian; Eka Pratiwi Briant Pakiding (Journal of Economics, Management, and Accounting, 2025)
Indonesia’s energy transition represents a strategic pathway to achieving regional economic resilience amid global decarbonization pressures and declining dependence on fossil resources. This study examines the relationship between renewable energy policy, fiscal capacity, and political commitment in shaping regional macroeconomic stability. Using a qualitative descriptive–analytical approach, the analysis draws on official reports from the Ministry of Energy and Mineral Resources, the Ministry of Finance, the National Energy Council, and institutional research publications. The findings indicate that renewable energy development remains below national targets, with uneven regional outcomes influenced by variations in fiscal strength and political consistency. Regions with higher fiscal capacity and stable governance tend to demonstrate better adaptability to energy transition policies, resulting in improved investment flows and economic diversification. Conversely, areas with limited fiscal resources and fragmented policy commitment experience slower transformation and weaker resilience. Strengthening local fiscal frameworks and institutional alignment is crucial to ensure that renewable energy policy contributes not only to national energy security but also to sustainable and inclusive regional economic growth.